"As Long as the Grass Grows, and the Sun Walks" - Caroline Ryan-York (Spectrum)
We all have a shared history of Land Acknowledgements. Settler Canadians are familiar with their use, but they may not understand their meaning. This essay stems from a collective frustration with improper Land Acknowledgments, and how they now produce more harm than good. This essay asks, what do Land Acknowledgements within Treaty 6 achieve in terms of reconciliation for Indigenous peoples? By looking at specific acknowledgements from organizations in Edmonton, I argue that these institutional acknowledgements are not rooted in reconciliation, but rather they are based upon false allyship with Indigenous Peoples. These rather script-like texts teach us that Land Acknowledgements have been re-imagined in a colonial view. By promoting settler discomfort within Land Acknowledgements, Canadians can begin to educate themselves on the basis of land and what the words within these acknowledgements mean for Indigenous reconciliation.